2007
DOI: 10.1182/blood.v110.11.2043.2043
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine Versus Chlorambucil in Treatment-Naive Patients with B-Cell Chronic Lymphocytic Leukemia (B-CLL): Results of an International Phase III Study.

Abstract: Introduction: Bendamustine (BEN) is a purine analog / alkylator hybrid agent with a particular mechanisms of action that provides effective treatment for a number of hematologic and non-hematologic malignancies. It is used primarily for chemo-naïve, relapsed or refractory B-CLL as well as for other types of non-Hodgkin’s lymphomas. The aim of this randomized phase III, open-label, multicenter study was to compare the efficacy and safety of BEN versus chlorambucil (CLB) in treatment-naïve patients (pts) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In a recent European Intergroup CLL Study, 305 previously untreated CLL patients under 75 years of age and requiring therapy were randomized to bendamustine 100 mg/m 2 intravenously for 2 consecutive days or oral chlorambucil 0.8 mg/kg on days 1 and 15 of each cycle. 34 The median age was 65 years; 70% had Binet stage B and 30% stage C disease. Overall response rates (ORR) in 156 bendamustine-and 149 chlorambucil-treated patients were 68% (30% complete remission [CR]) and 39% (2% CR), respectively (P Ͻ .0001).…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent European Intergroup CLL Study, 305 previously untreated CLL patients under 75 years of age and requiring therapy were randomized to bendamustine 100 mg/m 2 intravenously for 2 consecutive days or oral chlorambucil 0.8 mg/kg on days 1 and 15 of each cycle. 34 The median age was 65 years; 70% had Binet stage B and 30% stage C disease. Overall response rates (ORR) in 156 bendamustine-and 149 chlorambucil-treated patients were 68% (30% complete remission [CR]) and 39% (2% CR), respectively (P Ͻ .0001).…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…37 The recommended dose of bendamustine for previously untreated patients with CLL is 100 mg/m 2 on days 1 and 2 every 4 weeks. 34…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…Researchers from a phase III study evaluated bendamustine in treatment-naïve patients with CLL. 9 Their study showed a positive response for bendamustine versus chlorambucil, with manageable toxicity at a dose of 100 mg/m 2 on days 1 and 2 given every 28 days.…”
Section: Place In Therapymentioning
confidence: 96%
“…3 First-line treatment options for CLL include the those listed in Table 1. 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In patients with advanced CLL requiring treatment, the 2009 National Comprehensive Cancer Network (NCCN) guidelines recommend several options, including chemotherapy and chemoimmunotherapy. Unfortunately, none of these regimens are curative; therefore, research is focused on developing treatment options for patients with newly diagnosed disease and for patients receiving firstline therapy whose disease continues to progress.…”
Section: Outline Pharmacology Pharmacokinetics Drug Interactions Clinmentioning
confidence: 99%
See 1 more Smart Citation